ACTN3 R577X polymorphism in top-level Polish rowers - Cieszczyk, P.; Sawczuk, M.; Maciejewska-Karlowska, A.; Ficek, K. (Journal of Exercise Science & Fitness, 2012)
The first evidence that a mononucleotide difference in DNA sequence was associated with power ability referred to the R577X polymorphism of the ACTN3 gene, where translation (C > T) at nucleotide position 1747 in the ACTN3 coding sequence converts an arginine (R) to a stop codon (X) at residue 577. In the present study, DNA polymorphism derived from the ACTN3 gene was studied in Polish rowers to examine the hypothesis that the ACTN3 genotype is associated with athletic performance. The study involved 80 male Polish rowers of a nationally competitive standard and 204 unrelated volunteers for controls. Genotype distribution among the whole group of athletes (53.8% RR, 38.8% RX, 7.4 XX% DD) was significantly different to that among controls (36.3% RR, 46.1% RX, 17.6%; p ¼ 0.01). When only elite rowers were considered, p value for genotype distribution (56.8% RR, 37.8% RX, 5.4% XX) was 0.03. The genotype distribution among nonelite rowers (52.2% RR, 39.1% RX, 8.7% XX) was not significantly different to that among controls ( p ¼ 0.09). A significant excess of the 577R allele was noted in the whole cohort of rowers (73.11%, p ¼ 0.002). This trend was similar when comparing with the controls (59.3%) the allele frequency in elite rowers (75.7%, p ¼ 0.007) and nonelite rowers (71.7%, p ¼ 0.026). In conclusion, our results are contrary to the hypothesis that the ACTN3 577X allele may have some beneficial effect on endurance performance in rowing. On the contrary, the ACTN3 RX or RR genotypes seem to be a requirement for being an elite rower, therefore, identification of ACTN3 polymorphism as a genetic marker for rowing talent should be interpreted with great caution.